Pengembangan Lembar Kegiatan Peserta Didik Berbasis Kearifan Lokal Batik Bojonegoro Untuk Meningkatkan Keterampilan Berpikir Kreatif Dan Pemecahan Masalah IPS Kelas IV Sekolah Dasar - Ratna Nurma Yunita; Mustaji; Rr. Nanik Setyowati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to: (1) test the feasibility of LKPD based on local wisdom of Bojonegoro batik for fourth grade students at SD Negeri Grebegan Bojonegoro, (2) testing the practicality of LKPD based on local wisdom of Bojonegoro batik as a support material for the beauty of diversity in my country on the theme of 7th grade IV SD, (3) testing the effectiveness of LKPD based on local wisdom of Bojonegoro batik to improve creative thinking skills on theme 7th grade IV SD, (4) testing the effectiveness of LKPD based on local wisdom of Bojonegoro batik to improve problem solving ability on theme 7 grade IV SD. This learning media development research refers to the ADDIE model. The subjects of the study were fourth grade students of SD Negeri Grebegan with a total of 28 children. This research design uses One-Shot Case Study to measure creative thinking ability and One-Group Pretest-Posttest to measure problem solving ability. The results of this study indicate (1) that the learning device in the form of a syllabus obtained a validation result of 85.71% and was included in the "very feasible" category with the intention of being very feasible to use. For learning tools in the form of the Learning Implementation Plan (RPP) the validation results are 83.33%, so that it is included in the "very feasible" category, with the intention of being very feasible to use. Based on the results of material validation on the content of the LKPD material based on local wisdom, Bojonegoro batik received an assessment of 83.33%, and was included in the "very feasible" category, it means that the material included in the pre and posttest questions in the LKPD was declared to have included the eligibility requirements to be tested. to students. (2) there is an increase in class of 0.52%, according to the classification of the GScore table there is an increase with a moderate range of values ​​from pre test and post test scores, this is because there are some children who do not experience an increase in post test scores and there are also high scores. Thus, it can be concluded that learning using LKPD media based on local wisdom of Bojonegoro batik shows an increase in student learning outcomes.